CLC gene family in Solanum lycopersicum: genome-wide identification, expression, and evolutionary analysis of tomato in response to salinity and Cd stress - Ma, Jun; Li, Shan; Zaman, Shah; Anwar, Ali (Frontiers in Plant Science, 2025)
IntroductionChloride channels (CLCs) play critical roles in anion transport, stress adaptation, and ion homeostasis in plants. Whereas their genomic wide indentification and functional divergence in tomato (Solanum lycopersicum) remain largely unexplored.Methods and resultsIn this study, we identified nine CLC genes in the tomato genome, classifying them into two evolutionarily distinct clades (Group I and II) based on phylogenetic analysis. Structural dissection revealed conserved transmembrane domains (9–12 TMDs) and motif patterns (e.g., motifs 3/7/9 in Group I), with SlCLC02 exhibiting the largest gene size (27,041 bp). Promoter analysis indicated the presence of key abiotic stress-responsive cis-elements (ABRE, MYB, MYC), aligning with the pronounced transcriptional dynamics of SlCLCs under salinity stress. Notably, qRT-PCR analysis demonstrated that most SlCLC genes (particularly SlCLC05, an ortholog to AtCLC-g) exhibited rapid upregulation within 1-4 hours followed by downregulation in roots under salinity treatment, suggesting early stress signaling roles. Likewise, preliminary expression profiling under cadmium stress further identified specific induction of SlCLC07, proposing gene-specific roles in heavy metal detoxification. Strikingly, SlCLC09 lacked collinearity with Arabidopsis/potato homologs, implying lineage-specific diversification. DiscussionThese findings elucidate the SlCLC family’s structural diversity, evolutionary constraints, and stress-responsive regulation, providing a framework for targeting specific SlCLC genes (e.g., SlCLC05) to enhance chloride homeostasis in crops under combined salinity and cadmium stress. This study will open a new research direction for genetic crop improvement to ensure protected vegetable production.